Hierarchical pore metal-based catalytic adsorbent as well as preparation method and application thereof
By combining the sol-gel method and soft template method, a catalytic adsorbent with multi-stage pore structure and highly dispersed active metals was prepared, which solved the problems of single pore structure and uneven dispersion of active metals in the prior art, and significantly improved the catalytic activity and agent life.
Patent Information
- Application Number
- CN202411749979.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-14
AI Technical Summary
The existing metal-based catalytic adsorbents have problems with single pore structure and uneven dispersion of active metals, resulting in insufficient utilization of catalytic active sites and rapid catalyst deactivation.
The combination of sol-gel method and soft template method is adopted. By adding soft template agent before forming the gel and adding ammonia water appropriately during the aging process, the dispersion of multi-stage pore structure and active metal are precisely controlled.
Catalytic adsorbents with multi-stage pore structure and highly dispersed active metal components were prepared, which increased the specific surface area, pore volume and catalytic activity and extended the life of the catalyst.
Smart Images

Figure CN119608098A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic adsorbents for gas purification, and in particular to a multi-level porous metal-based catalytic adsorbent and a preparation method and application thereof. Background Art
[0002] In the prior art, traditional metal-based catalytic adsorbents often have the problem of a single pore structure. For example, some adsorbents that only have a microporous structure, although the micropores have a large specific surface area and have a good adsorption capacity for small molecules, have a large diffusion resistance for macromolecular reactants or products, which easily leads to the inability to fully utilize the active sites of the catalyst, and easily causes pore blockage, causing the catalyst to deactivate faster. Adsorbents that only have macroporous or mesoporous structures, such as Chinese patent CN118649703A, disclose a mesoporous carrier-based supported catalyst and a preparation method thereof, using a block copolymer as a template to prepare a catalyst precursor, and then mixing the catalyst precursor, a metal salt solution, and β-cyclodextrin to obtain a mesoporous carrier-based supported catalyst, which has a relatively small specific surface area and limited adsorption capacity, and is also difficult to meet the needs of complex reaction systems.
[0003] In addition, the dispersion of active metal components is also a difficult problem when preparing metal-based catalytic adsorbents. If the active metal is not evenly dispersed on the carrier, it is easy to form agglomerates, which will reduce the effective utilization rate of the active metal on the one hand, and on the other hand, the agglomerated metal particles may change the selectivity of the reaction, or even induce side reactions, reducing the overall performance of the catalytic adsorbent.
[0004] The sol-gel method is a commonly used material preparation method, which can evenly mix metal precursors in a solution and form a gel network structure through reactions such as hydrolysis and condensation. However, it is difficult to accurately control the multi-level pore structure of the material using the simple sol-gel method. The soft template method uses some soft template agents with self-assembly capabilities, such as surfactants, block copolymers, etc., to form a specific ordered structure in the solution to guide the growth of the material and the formation of the pore structure. However, when the soft template method is used alone, there may be problems such as incomplete removal of the template agent, affecting the material performance, and insufficient precision in regulating the dispersion of the metal active components. Summary of the invention
[0005] Therefore, in order to solve the problems in the prior art, the present invention combines the advantages of the sol-gel method and the soft template method to propose an integrated preparation method, which can prepare a metal-based catalytic adsorbent with a multi-level pore structure and highly dispersed active metal components. The specific scheme is as follows:
[0006] A method for preparing a multi-level porous metal-based catalytic adsorbent comprises the following steps:
[0007] Step 1: Slowly add the soft template to a 0.08-0.09 g / mL ethanol solution of the metal precursor under stirring, and stir until it is completely dissolved to form a uniform solution A;
[0008] Step 2: slowly adding tetraethyl orthosilicate (TEOS) to the ethanol solution of the acid catalyst, stirring and hydrolyzing at 30-50° C. for 1-3 hours to obtain solution B, wherein the volume ratio of the ethanol solution of the acid catalyst to the ethanol solution of the metal precursor is 1-1.05:1, and the mass ratio of tetraethyl orthosilicate to the metal precursor is 1:0.15-0.30;
[0009] Step 3: Slowly add solution B, surfactant and chelating agent into solution A at the same time, and continue stirring at 30-50°C for 2-5 hours to react and form a gel;
[0010] Step 4: placing the gel obtained in step 3 in a sealed container and aging at 50-80° C. for 12-24 hours, adding a base catalyst dropwise thereto after aging for 8-12 hours, and drying in an oven at 80-120° C. for 12-24 hours after aging to obtain a dried sample;
[0011] Step 5: calcine the dried sample once in a nitrogen or argon atmosphere at a temperature of 300-400°C, a calcination time of 3-8h, and a gas flow rate of 30-80mL / min; then calcine it twice in an air atmosphere at a temperature of 500-700°C, a calcination time of 2-5h, to obtain a multi-level porous metal-based catalytic adsorbent.
[0012] Furthermore, the metal precursor in step 1 is one or more of a soluble calcium salt, a soluble nickel salt, a soluble magnesium salt, a soluble iron salt, and a soluble europium salt.
[0013] Furthermore, the soluble calcium salt, soluble nickel salt, soluble magnesium salt, soluble iron salt, and soluble europium salt are one or more of nitrate, oxalate, acetate, and carbonate.
[0014] Furthermore, the soft template in step 1 is one or more of polystyrene, sodium dodecyl sulfate, dodecyltrimethylammonium bromide, and block copolymers, and the mass ratio of the soft template to the tetraethyl orthosilicate is 0.075-0.15:1.
[0015] Furthermore, the acid catalyst in step 2 is 30% hydrochloric acid, and the volume ratio of 30% hydrochloric acid to ethanol in the ethanol solution of the acid catalyst is 0.028-0.035:1.
[0016] Furthermore, the surfactant in step 3 is one or more of lauroyl glutamic acid, sodium alginate, polyvinyl alcohol, fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide, and the concentration of the surfactant after addition is 0.07-0.1 g / mL.
[0017] Furthermore, the chelating agent in step 3 is one or more of triethyl citrate, disodium ethylenediaminetetraacetate, citric acid, and sodium gluconate, and the concentration of the chelating agent after addition is 0.14-0.2 g / mL.
[0018] Furthermore, in step 4, the alkaline catalyst is aqueous ammonia, and the volume ratio of aqueous ammonia to the gel is 1:40-42.
[0019] The multi-level porous metal-based catalytic adsorbent prepared according to the above method comprises metal-based particles and a catalytic adsorbent carrier, wherein the metal-based particles are one or more of calcium, nickel, magnesium, iron, europium and their corresponding metal oxides, and the catalytic adsorbent carrier has a microporous, mesoporous and macroporous structure, wherein the micropore diameter is 0.5-2nm, the mesopore diameter is 3-50nm, and the macropore diameter is 200-1000nm, the micropores account for 60-80%, the mesopores account for 15-35%, and the macropores account for 5-25%, and the specific surface area of the multi-level porous metal-based catalytic adsorbent is greater than 130m 2 / g, and the pore volume is greater than 0.4cc / g.
[0020] The multi-level porous metal-based catalytic adsorbent can be used for gas purification, specifically for removing H from hydrogen and inert gases. 2 O, O 2 ,CO,CO 2 .
[0021] The beneficial effects of the present invention are:
[0022] (1) In the preparation method of the present invention, a template is added before the gel is formed. The template molecules can be dispersed relatively evenly in the initial solution. As the precursor undergoes hydrolysis, polycondensation and other reactions to gradually form a gel, the space occupied by the template will guide the formation of a pore structure distributed around it, which is more conducive to accurately controlling the pore size and distribution. In addition, adding the template first can enable it to fully interact with the precursor, play a role in guiding the formation of pores throughout the hydrolysis and polycondensation of the precursor, and maximize its template effect, so that the final catalytic adsorbent mesoporous structure is closer to the ideal state designed by the template, ensuring a high template utilization rate, and effectively improving the performance indicators such as pore regularity and specific surface area.
[0023] (2) In addition, CO, CO 2 , H 2 O, O 2The kinetic diameters of impurity gases are all 0.2-0.4nm. Therefore, during the aging process, adding a proper amount of ammonia water can promote the formation of micropores. The specific surface area of the micropores is the largest among the three pore structures, which can provide the most catalytic adsorption active sites, increase the specific surface area and pore volume, and improve the adsorption and catalytic ability of the catalytic adsorbent for molecules of different sizes. In addition, ammonia water helps to evenly disperse the precursor and the formed particles in the solution to prevent agglomeration, so that the prepared catalytic adsorbent has a more uniform pore structure and active site distribution, and improves the consistency and stability of its catalytic adsorption performance. In addition, ammonia water, as a catalyst, can accelerate the hydrolysis and condensation reaction rate of the precursor, so that the reaction can reach the desired gel state in a shorter time, thereby improving the preparation efficiency.
[0024] (3) Compared with the traditional high-temperature solid-phase reaction and other preparation methods, the sol-gel method of the preparation method of the present invention usually reacts at a lower temperature, reduces energy consumption, and has relatively low requirements for equipment. The use of soft templates further reduces the harsh conditions in the preparation process, avoids the problems of sintering of active components and destruction of carrier structure caused by high temperature and other conditions, and is conducive to maintaining the performance of the catalytic adsorbent.
[0025] (4) The multi-level porous metal-based catalytic adsorbent (i) prepared by the method of the present invention has excellent pore structure characteristics, including multi-level pore structures of different scales such as micropores, mesopores and macropores, which increases the specific surface area and provides more active sites, which is beneficial to the adsorption of reactant molecules and the desorption of product molecules, thereby improving the activity of the catalytic adsorbent. At the same time, the pores are evenly distributed and the pore size is adjustable, which can be customized according to different reaction requirements, so that the catalytic adsorbent has better selectivity for reactant molecules; (ii) Good dispersion of active components: During the sol-gel formation process, the metal precursors can be evenly mixed in the solution to achieve uniformity at the molecular level. Combined with the confinement effect of the soft template, the metal active components can be highly dispersed on the carrier, avoiding agglomeration, improving the utilization rate of the active components, and thus enhancing the activity and stability of the catalytic adsorbent; (iii) Uniform doping of components: The sol-gel method can easily and evenly and quantitatively incorporate some trace elements to achieve uniform doping at the molecular level. The catalytic adsorbent can be modified by adding different metal additives to further optimize the performance of the catalytic adsorbent and improve its catalytic activity, selectivity and stability; (iv) Controllable morphology and size: With the help of the spatial confinement effect of the soft template and the control of the chemical reaction in the sol-gel process, the morphology and size of the catalytic adsorbent can be precisely controlled to prepare a catalytic adsorbent with a specific shape and size to meet the requirements of different reaction systems for the morphology and size of the catalytic adsorbent, thereby improving the adsorption efficiency of the catalytic adsorbent. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0027] Figure 1 The schematic diagram of the structure of the multi-level porous metal-based catalytic adsorbent of the present invention is shown;
[0028] Figure 2 The SEM image of the multi-level porous metal-based catalytic adsorbent in Example 1 of the present invention is shown;
[0029] Figure 3 The SEM image of the multi-level porous metal-based catalytic adsorbent in Example 2 of the present invention is shown;
[0030] Figure 4 The SEM image of the multi-level porous metal-based catalytic adsorbent in Comparative Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] Example 1
[0033] (1) 0.55 g of nickel nitrate and 0.3 g of magnesium nitrate solution were dissolved in 10 mL of anhydrous ethanol, and 0.425 g of a soft template agent, hexadecyltrimethylammonium bromide, was slowly added under stirring, and stirred until completely dissolved to form a uniform solution A;
[0034] (2) 3 g of tetraethyl orthosilicate (TEOS) was slowly added to another solution containing 10 mL of anhydrous ethanol and 0.3 mL of hydrochloric acid, and the mixture was stirred and hydrolyzed at 40° C. for 1.5 h to obtain solution B;
[0035] (3) Solution B was slowly added to Solution A, and 2 g of lauric acid glutamic acid and 3 g of triethyl citrate were added at the same time, and the mixture was stirred at 40° C. for 4 h to react and form a gel;
[0036] (4) placing the gel in a sealed container and aging at 60°C for 18 h, adding 0.5 mL of aqueous ammonia to the gel after aging for 8 h, and then drying the gel in an oven at 120°C for 12 h;
[0037] (5) The dried sample was placed in a tubular furnace with nitrogen (nitrogen flow rate of 50 mL / min) as a protective atmosphere at 320°C for 4 hours to perform a primary calcination to obtain a catalytic adsorbent intermediate after template treatment; the catalytic adsorbent intermediate was placed in a muffle furnace with air as an atmosphere at 650°C for 3 hours to perform a secondary calcination to obtain a multi-level porous metal-based catalytic adsorbent.
[0038] Example 2
[0039] The difference between this embodiment and embodiment 1 is that the ratio of the metal precursor and the template-gel is different, and the rest of the preparation methods are the same.
[0040] (1) 0.35 g of nickel nitrate and 0.5 g of cobalt nitrate solution were dissolved in 10 mL of anhydrous ethanol, and 0.38 g of soft template agent hexadecyltrimethylammonium bromide was slowly added under stirring conditions, and stirred until it was completely dissolved to form a uniform solution A;
[0041] (2) 5 g of tetraethyl orthosilicate (TEOS) was slowly added to another solution containing 10 mL of anhydrous ethanol and 0.3 mL of hydrochloric acid, and the mixture was stirred and hydrolyzed at 40° C. for 1.5 h to obtain solution B;
[0042] (3) Solution B was slowly added to Solution A, and 1.5 g of lauric glutamic acid and 4 g of triethyl citrate were added at the same time, and the mixture was stirred at 40° C. for 4 h to react and form a gel;
[0043] Steps 4-5 are the same as in Example 1.
[0044] Comparative Example 1 (Preparation of Catalytic Adsorbent by Single Template Method)
[0045] (1) Add 10 g of polyvinyl pyrrolidone into 250 mL of deionized water and stir to dissolve it to obtain solution A;
[0046] (2) adding 30 mL of styrene monomer to solution A, stirring evenly, adding 1 g of benzoyl peroxide, and performing a polymerization reaction at 60° C. to obtain a polymer;
[0047] (3) After the reaction is completed, the product is placed in a centrifuge at 5000 rpm for centrifugal separation, and then the centrifuged product is placed in a vacuum drying oven at 80° C. for 10 h to obtain a polymer template;
[0048] (4) dissolving 2 g of sodium alginate in a mixed solution of 1.5 g of deionized water and 9 g of ethanol, stirring to fully dissolve, and then adding 0.3 g (2 mol / L) of HCl and 3 g of a silicon dioxide precursor (TEOS) solution to obtain a solution B;
[0049] (5) 6 g of the polymer template was immersed in solution B, and the product obtained after suction filtration and drying was placed in a crucible, placed in a tube furnace, and heated to 500° C. at a rate of 5° C. / min in an air atmosphere and kept at this temperature for 8 h. After the furnace was cooled to room temperature, a hierarchical porous carrier was obtained;
[0050] (6) Weigh 0.65 g of nickel nitrate and dissolve it in deionized water to prepare a metal precursor solution;
[0051] (7) The hierarchical porous support is impregnated with the metal precursor solution, and after impregnation, it is placed in a vacuum drying oven at 80°C for 10 h. The product obtained after drying is then loaded into a crucible, placed in a tubular furnace, and heated to 500°C at a rate of 10°C / min in a nitrogen atmosphere and kept warm for 10 h. After the furnace is cooled to room temperature, a hierarchical porous nickel-based catalytic adsorbent is obtained.
[0052] Figure 2-4 The SEM images of the multi-level pore structure catalytic adsorbents prepared in Example 1, Example 2 and Comparative Example 1 respectively show that the multi-level pore channel structure of the catalytic adsorbent prepared by the integrated gel-template method of the present invention is richer, and the dispersion of the active components in the multi-level pore channel is better.
[0053] Table 1 Specific surface area, pore volume and pore size of catalytic adsorbents prepared by different methods
[0054]
[0055]
[0056] It can be seen from Table 1 that the active components in the catalytic adsorbent prepared by the integrated gel-template method of the present invention have better dispersibility and larger specific surface area.
[0057] Table 2 CO and CO in hydrogen after purification by catalytic adsorbent 2 The concentration (the raw gas contains 50ppm CO and 50ppmCO 2 of hydrogen)
[0058] CO(ppm) <![CDATA[CO 2 (ppm)]]> Example 1 8 12 Example 2 8.5 13.2 Comparative Example 1 15 18
[0059] It can be seen from Table 1-2 that the catalytic adsorbent prepared by the integrated gel-template method of the present invention has better adsorption performance for impurity gases due to its better specific surface area and catalytic activity.
[0060] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A multi-level porous metal-based catalytic adsorbent, characterized in that: The invention comprises metal-based particles and a catalytic adsorbent carrier, wherein the metal-based particles are one or more of calcium, nickel, magnesium, iron, europium and their corresponding metal oxides, and the catalytic adsorbent carrier has a microporous, mesoporous and macroporous structure, wherein the micropore diameter is 0.5-2nm, the mesopore diameter is 3-50nm, and the macropore diameter is 200-1000nm, the micropores account for 60-80%, the mesopores account for 15-35%, and the macropores account for 5-25%, and the specific surface area of the multi-level porous metal-based catalytic adsorbent is greater than 130m 2 / g, and the pore volume is greater than 0.4cc / g.
2. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 1, characterized in that: The following steps are involved: Step 1: Slowly add the soft template to a 0.08-0.09 g / mL ethanol solution of the metal precursor under stirring, and stir until it is completely dissolved to form a uniform solution A; Step 2: slowly adding tetraethyl orthosilicate to the ethanol solution of the acid catalyst, stirring and hydrolyzing at 30-50° C. for 1-3 hours to obtain solution B, wherein the volume ratio of the ethanol solution of the acid catalyst to the ethanol solution of the metal precursor is 1-1.05:1, and the mass ratio of the tetraethyl orthosilicate to the metal precursor is 1:0.15-0.30; Step 3: Slowly add solution B, surfactant and chelating agent into solution A at the same time, and continue stirring at 30-50°C for 2-5 hours to react and form a gel; Step 4: placing the gel obtained in step 3 in a sealed container and aging at 50-80° C. for 12-24 hours, adding a base catalyst dropwise thereto after aging for 8-12 hours, and drying in an oven at 80-120° C. for 12-24 hours after aging to obtain a dried sample; Step 5: calcine the dried sample once in a nitrogen or argon atmosphere at a temperature of 300-400°C, a calcination time of 3-8h, and a gas flow rate of 30-80mL / min; then calcine it twice in an air atmosphere at a temperature of 500-700°C, a calcination time of 2-5h, to obtain a multi-level porous metal-based catalytic adsorbent.
3. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: The metal precursor in step 1 is one or more of a soluble calcium salt, a soluble nickel salt, a soluble magnesium salt, a soluble iron salt, and a soluble europium salt.
4. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 3, characterized in that: The metal precursor is one or more of nitrate, oxalate, acetate and carbonate.
5. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: The soft template in step 1 is one or more of polystyrene, sodium dodecyl sulfate, dodecyltrimethylammonium bromide, and block copolymers, and the mass ratio of the soft template to the tetraethyl orthosilicate is 0.075-0.15:
1.
6. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: The acid catalyst in step 2 is 30% hydrochloric acid, and the volume ratio of 30% hydrochloric acid to ethanol in the ethanol solution of the acid catalyst is 0.028-0.035:
1.
7. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: The surfactant in step 3 is one or more of lauroyl glutamic acid, sodium alginate, polyvinyl alcohol, fatty alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and hexadecyltrimethylammonium bromide, and the concentration of the surfactant after addition is 0.07-0.1 g / mL.
8. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: The chelating agent in step 3 is one or more of triethyl citrate, disodium ethylenediaminetetraacetate, citric acid, and sodium gluconate, and the concentration of the chelating agent after addition is 0.14-0.2 g / mL.
9. The method for preparing a multi-level porous metal-based catalytic adsorbent according to claim 2, characterized in that: In step 4, the base catalyst is ammonia water, and the volume ratio of ammonia water to the gel is 1:40-42.
10. The use of a multi-level porous metal-based catalytic adsorbent in gas purification according to claim 1, characterized in that: Used to remove H2O, O2, CO, CO2 from hydrogen and inert gases.
Citation Information
Patent Citations
Supported catalyst based on mesoporous carrier and preparation method thereof
CN118649703A
Cited By
Carbon dioxide adsorbent as well as preparation method and application thereof
CN120459941A
Purifying agent prepared based on solid waste and application method
CN121553939A
Fly ash-based multiple-effect catalyst and preparation method thereof
CN121623786A
Fly ash-based multi-effect catalysts and their preparation methods
CN121623786B